TAD’s for the Derotation of 90° Rotated Maxillary Bicuspids - Hasan Sabah Hasan; Ayshan Kolemen; Mohamed Elkolaly; Anand Marya; Shreyas Gujjar; Adith Venugopal (Case Reports in Dentistry)
It is undeniable that the advent of extra-alveolar mini-implants for anchorage purposes has revolutionized the field of Orthodontics. This case report sheds light on an innovative anchorage plan using TADs, to carry out treatment for a 15-year-old female patient. The patient reported to the clinic with a chief complaint of rotated second premolars, crowding, and a deep bite. On examination, it was seen that the patient had a Class I skeletal pattern, Class II subdivision molar relationship, 90-degree maxillary second premolar rotations, crowding in both the arches, and a deep bite. In this case, the clinicians decided to use TADs for premolar derotation as it not only provides a pure rotational couple without any deleterious effects on the adjacent teeth but also helps shorten the overall treatment time. The total treatment time for this case was 10 months.